Burn scar pain: from mechanisms to treatments - Zhao, Minjuan (Frontiers in Physiology, 2025)
Chronic scars and pain following burns not only impair patients’ quality of life but also resist current empirical treatments, highlighting an urgent need for mechanism-based therapies. Early studies have characterized key mediators of scar fibrosis and nociception, yet integration of molecular and neural pathways remains limited. Here, we comprehensively review 1 molecular and cellular drivers of burn scar formation—particularly transforming growth factor-β (TGF-β)–induced fibroblast activation and extracellular matrix remodeling; 2 bidirectional interactions between scar tissue and nerve regeneration via neuropeptides (Nerve growth factor, Substance P, calcitonin gene-related peptide); 3 mechanisms underpinning long-term scar pain, including peripheral/central sensitization through TRPV1/Nav channels and neuroinflammation; and 4 emerging treatments—such as laser, extracorporeal shock wave therapy (ESWT), regenerative injections, and transient receptor potential (TRP) antagonists—that target these pathways. We conclude that a detailed understanding of scar–nerve crosstalk at the molecular level is pivotal for developing targeted interventions and improving long-term outcomes.